An investigation into the impact of deleting one copy of the glutaredoxin-2 gene on diet-induced weight gain and the bioenergetics of muscle mitochondria in female mice fed a high fat diet - Robert Gill; Sarah Mallay; Adrian Young; Ryan J. Mailloux (Taylor & Francis Group, 2020)
Our group recently documented that male mice containing a deletion for one copy of the glutaredoxin-2 (Grx2) gene were completely protected from developing diet-induced obesity (DIO). Objectives: Here, we conducted a similar investigation but with female littermates. Results: In comparison to our recent publication using male mice, exposure of WT and GRX2+/- female mice to a HFD from 3-to-10 weeks of age did not induce any changes in body mass, circulating blood glucose, food intake, hepatic glycogen levels, or abdominal fat pad mass. Examination of the bioenergetics of muscle mitochondria revealed no changes in the rate of superoxide (O2●−)/hydrogen peroxide (H2O2) or O2 consumption under different states of respiration or alterations in lipid peroxidation adduct levels regardless of mouse strain or diet. Additionally, we measured the bioenergetics of mitochondria isolated from liver tissue and found that partial loss of GRX2 augmented respiration but did not alter ROS production. Discussion: Overall, our findings demonstrate there are sex differences in the protection of female GRX2+/- mice from DIO, fat accretion, intrahepatic lipid accumulation, and the bioenergetics of mitochondria from muscle and liver tissue.